O sentido da vida, a religiosidade e os valores na cultura surda - Oliveira, Karen Guedes (2014)
This work was of the view that deaf people constitute a genuine culture, post signs that share as the Brazilian Sign Language (Libras). Given the scarcity of studies on the culture in psychometric perspective, the goal of this dissertation was initially adapt and validate the questionnaire Meaning of Life, Religious Attitudes Scale and Basic Values Questionnaire for Deaf people. Therefore, it was necessary linguistic these instruments. In a second step, aimed at investigating the possible associations between factors such instruments. Counted on 200 Deaf 9 states of Brazil: Paraiba (69%), Rio Grande do Norte (5.5%), Pernambuco (3.5%), Ceará (4%), Rio Grande do Sul (4, 5%), Paraná (4.5%), Minas Gerais (2%), São Paulo (5%) and Mato Grosso (2%). The sample had a mean age of 28.6 (SD = 7.16), ranging 18-56 years, the majority were male (58%). Data collection occurred both online and face shape. The results suggested that the instruments are relevant to the given context of deaf culture and that the variables religiosity variables , the meaning of life and human values were associated in a direct and significant. The results were discussed in light of the existential analysis of Viktor Frankl and the Functionalist Theory of Human Values